The dispositif of citizenship: technology and personhood in Iain M. Banks's culture. Issue 10 (3rd October 2022) - Merryman, Walter
ABSTRACT: This essay examines concepts of personhood and citizenship in Iain M. Banks's science fiction novels Surface Detail and The Hydrogen Sonata, both set in the fictional utopia of the Culture. Although personhood is often described as a quality inherent to human beings, this essay will show how the novels represent that concept of personhood and subsequent practices of citizenship as contingent on the Culture's technology. The essay draws on theories of the dispositif to describe personhood and technology and proposes a distinction between technical and conceptual dispositifs. Drawing on Carl Freedman's work on science fiction, I deploy the reading of the novels as a utopian theory that offers a critical perspective on Hannah Arendt's work on human rights and citizenship and on the work of philosophers who have sought to develop more inclusive normative concepts of personhood. Although these philosophers have done significant philosophical work to develop more inclusive conceptual dispositifs, the utopian critique created by the novels suggests that our thinking would be better directed toward the technology used to put those concepts into practice. The last section of the essay shows how Surface Detail represents the Culture's technology creating a form of 'extraterritorial' citizenship.